Endoscopic retrieval of gastric and oesophageal foreign bodies in 52 cats. (10th November 2019) - Dollo, V.; Chambers, G.; Carothers, M.
Abstract : Objectives: To assess the outcomes and major complications in cats that require oesophageal and gastric endoscopic foreign body removal. Materials and Methods: The medical records of 52 cats with oesophageal and gastric foreign bodies that underwent endoscopic foreign body retrieval during a 13‐year period (2006 to 2018) were retrospectively reviewed to characterise the clinical and radiographic signs, endoscopic findings, outcomes and major complications. Results: Endoscopic foreign body retrieval was successful in 49 of the 52 cats (94.2%). Radiographs confirmed the foreign material in 24 of the 50 cats (48%). Major complications occurred in eight of the 52 cats (15.4%) and included pleural effusion (n=2), aspiration pneumonia (n=2), unsuccessful removal of foreign material with endoscopy (n=3), oesophageal stricture formation (n=3) and cardiopulmonary arrest (n=1). Cats with oesophageal foreign bodies were more likely to experience major complications than those with gastric foreign bodies. Clinical Significance: Endoscopic foreign body removal in cats was associated with good overall outcomes and a low complication rate in this study sample. These results will help veterinarians better understand the outcomes of endoscopic foreign body removal in cats.